STANDARDS AND EVALUATION INSTRUMENTS, ON THE RELEVANCE AND RELIABILITY OF THE RANKINGS OF UNIVERSITIES - Mejia Mejia, Elias (2020)
This research was conducted in order to establish influence that produced, in therelevance and reliability of the Rankings of universities, standards and evaluation instruments used to develop these rankings.Diversity of rankings, the diversity of criteria that are elaborated and the diversity ofagencies that produce them is the greatest indicator that, in this respect, there is nouniformity or uniqueness that is conducive to objectivity and quality, so it has beenassumed in the next problem: How does affect the different standards and evaluationinstruments that apply specialized institutions, the relevance and the reliability of therankings of universities proposed?. After carrying out the fieldwork, which has consistedof reviewing specialized literature, collecting expert judgments, analyzing the respectivedocumentation and systematizing the information collected, the relationship betweenthe standards and instruments applied by different institutions with the relevance andreliability of the rankings of universities they propose.